OC-061 Change in size of hepatic colorectal metastases after completion of chemotherapy is greater than during treatment, but doesn't influence disease-free survival after resection. (22nd June 2015) - Wiggans, M; Lim, E; Shahtahmassebi, G; Aroori, S; Bowles, M; Briggs, C; Stell, D
Abstract : Introduction: The aim of this study was to assess the change in size of colorectal liver metastases between post-chemotherapy imaging and liver resection and to measure potential associations of this change with disease-free survival. Method: Analysis of a prospectively maintained database of patients undergoing liver resection for colorectal liver metastases between 2005 and 2012 was undertaken. Response to chemotherapy was assessed by RECIST criteria. Change in tumour size between completion of chemotherapy and liver resection was measured by comparing the maximum diameter of lesions determined by post-chemotherapy imaging and those determined by examination of the resected specimen. Results: In 146 patients the median interval between post-chemotherapy imaging and liver resection was 10.4 weeks (7.1–17.6 weeks). During this period tumour diameter increased in 102 patients (69.9%) and decreased in 37 (25.3%) with a median change of +2.3% per week (–19.4 to +1624%). Tumour behaviour after completion of treatment was not associated with disease-free survival in patients who initially responded to chemotherapy (P = 0.591) or those with stable disease (P = 0.436). Among patients with progressive disease after completion of chemotherapy the median disease-free survival of patients who initially responded (26 months) was longer than in those with stable disease (7 months) (P = 0.002), but there was no association between the rate of increase in size and disease-free survival (P = 0.406). Conclusion: Change in tumour size after completion of chemotherapy is variable and can be rapid, especially in patients who initially responded to treatment. It does not however appear to affect outcome and should not be considered an adverse factor when counselling patients. Disclosure of interest: None Declared.